Education transformation in Indonesia requires the implementation of differentiated learning - Rais Hidayat; Yuyun Elizabeth Patras (Institute of Advanced Engineering and Science, 2024)
This study describes teachers’ perceptions of implementing education transformation after the Corona Virus Disease 2019 (COVID-19) pandemic. The research method uses a mixed-method approach: quantitative and qualitative. Quantitative data collection using questionnaires. Analysis of quantitative data using the Rasch model. Qualitative data analysis through the collection, reduction, and presentation. The respondents of this research are 389 teachers in Indonesia. The questionnaire instrument contains 21 items of statements. Before being sent to teachers via the Google form, the questionnaire had met the readability test by 10 teachers. This research found that the most effortless education transformation is related to the education ecosystem. However, implementations still challenging to implement are related to pedagogy, especially the implementation of differentiated learning. Therefore, this study implies that the educational ecosystem needs to be maintained. Meanwhile, pedagogics, especially those related to differentiated learning, must be improved with various training to recognize student learning styles, multiple intelligences, learning readiness, teacher socio-emotional, and student socio-cultural.